Combating Smuggling: What Games We Are Playing: An Indonesian Case Study - Hidajat Hendarsjah (Universitas Sebelas Maret, 2016)
Intuitively, a person’s behavioral tendency to corrupt seems to follow several incentives that bound with the outcomes. But changes in outcomes’ payoffs do not always directly affect to person behavior. In games with mixed equilibrium presences, probability of actions taken by other parties (in this paper, “to inspect” and “do not inspect”) will alter a person tendency whether “to comply” or “to cheat”, as shown in garment smuggling case in Indonesia. Game theoretic concepts were employed in this paper to perform framework for analysis in describing the actions of interdependent agents. When the game has mixed equilibrium, probability of one player to take one strategic action does not depend on the opponent’s payoffs (i.e. maximum penalty). What does change is the probability of the opponent’s strategic actions.